A unique sequential C–S or N–S inductive cleavage and retro‐Diels‐Alder fragmentation mechanism for alkylsulfonyl piperidine‐ and piperazine‐containing compounds. (23rd June 2021) - Maw, Hlaing H.; Teitelbaum, Aaron M.; Yu, Hongbin
Abstract : Rationale: BI 605906 undergoes a collision‐induced dissociation (CID) fragmentation resulting in the loss of methylsulfinic acid and butadiene to produce a corresponding imine. The fragmentation is hypothesized to occur via inductive cleavage of the C–S bond, generating a six‐membered cyclic ene, followed by the retro‐Diels‐Alder (RDA) reaction. The aim of this study was to provide mechanistic evidence for the proposed fragmentation by investigating the CID spectra of BI 605906 and other alkylsulfonyl piperidine‐ and piperazine‐containing compounds. Methods: The positive electrospray ionization tandem mass spectrometric (ESI + ‐MS/MS) fragmentations of BI 605906, D9 ‐BI 605906, GK02935, GK02942, ketoconazole, terazosin, and homopiperazine were investigated. Additionally, incubations of BI 605906 and GK02942 in human liver microsomes (HLM) preparations were conducted. Metabolite identification experiments were performed following these incubations to investigate corresponding in vitro metabolism. Results: BI 605906, D9 ‐BI 605906, GK02935, and GK02942 demonstrated the same fragmentation pattern by generating a respective imine ion, supporting the hypothesized inductive cleavage and subsequent RDA mechanism. Ketoconazole and terazosin, which contain either an N ‐acetyl or tetrahydrofuranyl piperazine group, respectively, did not demonstrate this mechanism, notably because they do not have the alkylsulfonyl moiety as a good leaving group. Although homopiperazine contains an arylsulfonyl diazepane group, and the initial step produced an unsaturated diazepane ring, the subsequent RDA reaction was unable to proceed due to the absence of a six‐membered cyclic ene intermediate. Additionally, we identified oxidative metabolites of BI 605906 and GK02942 in HLM incubations utilizing the proposed fragmentation pattern. Conclusions: In the mass spectrometer, compounds containing alkylsulfonyl piperidine or piperazine groups can undergo inductive cleavage, leading to a six‐membered cyclic ene intermediate. This intermediate will then form a corresponding imine ion via the RDA reaction. A practical application of this work is to utilize this fragmentation for elucidating structures of metabolites arising from parent compounds containing alkylsulfonyl piperidine or piperazine moieties.